The Production of Key Chain Kaugaci (Keychain Cardboard) As A Development Effort Of Psychomotor Skills In Higher Education - Puji, Rully Putri Nirmala; Tholib, Abu; Kuswanto, Beki Febri; Firmansyah, Muhammad Reza; Syamsul, Achmad (International Journal of Scientific Research and Management (IJSRM), 2018)
Creativity is one of indicators in assessing learners’ competence and personality. Innovation skill and capability are expected to be developed continuously by learners in their learning environment. KAUGACI production was a keychain product by utilizing used goods in the form of cardboard, and it was developed by students of history education of Jember University. This research aims to assess the effectiveness of products in improving students’ psychomotor skills in the university level. 100 respondents with demographic profiles based on gender and entrepreneurial experience were taken as the research participants. The findings showed that KAUGACI products had high effectiveness and productivity that gave impact to the students’ skills development.